The Grammatical Systems of Attentionworthiness: Positional Signals and Invariant Meanings in Spanish Word Order - Ho-Fernández, Eduardo (ProQuest Dissertations & Theses, 2020)
This dissertation presents a Columbia School analysis of word order phenomena in Spanish. The data was sourced from a corpus of manually collected utterances extracted from six volumes of Latin American short stories written in the twentieth century. The study employs various qualitative and quantitative techniques in order to test the various hypotheses offered as explanations of the distributional problems selected for the study. The observations roughly correspond to word orders that the grammatical tradition describes as having to do with either verbs with one argument (SV, VS, OV, VO) or verbs with two arguments (SVO, OVS, VSO, VOS, SOV, OSV). However, the present analysis shows that word order in Spanish can best be accounted for by discarding the traditional notions Subject, Object and Verb (S, O, V) in favor of the notions of Event or (E) (a word inferred as an event or occurrence) and Participant or (P) (a word, phrase, or clause inferred as an entity involved in the occurrence), where Participant can equally be what the tradition would have called a Subject or what it would have called an Object. The study offers hypotheses that propose that the word orders under scrutiny are discrete signals of meanings of Attentionworthiness, which is defined as the relative degree of differential attention that the speaker wants paid to a Participant or an Event. Depending on the word order configuration, qualitative testing is performed on individual examples assessing the attention-grabbing merits of either the Participant(s) or the Event, while quantitative tests are designed to test for the general applicability of an explanation throughout the corpus. Two grammatical systems are hypothesized as representing grammatical features of Spanish: the system of Participant Attentionworthiness and the system of Event Attentionworthiness. Within these systems, HIGHER or LOWER Participant Attentionworthiness or MORE or LESS Event Attentionworthiness is allocated based on the position occupied by the Participant(s) or the Event within an utterance. The new typology (i.e., various combinations of P and E) represents the meaningful relationship between the categories proposed for the ordering phenomena and the signaling of a semantic or communicative instruction that is hypothesized for each word order.